(untitled) (Journal of Environmental Science and Natural Resources, 2021)
Temperature has great influence on the changes in physico-chemical and microbiological parameters of fish muscle. The present study was conducted to observe the changes in physico-chemical and microbiological parameters of pangas (Pangasius pangasius) muscle during ice storage. At the initial stage of storage TVBN-value was found 1.37mg/100g, peroxide value 1.1m.eq/kg of oil, breaking force 1005.67 (± 3.93g), protein solubility 86.37% and microbial load 7.6×103 CFU/g which reached to 28.25 mg/100g, 19 meq./kg of fish oil, 480.23 (± 0.88g), 36% and 4.6 ×106 CFU/g, respectively after 16 days of storage in ice. On the basis of the obtained results the study could be concluded as- pangas (Pangasius pangasius) can be stored in ice up to 16 days. Environ. Sci. & Natural Resources, 12(1&2): 199-208, 2019